2016
DOI: 10.1364/oe.24.007654
|View full text |Cite
|
Sign up to set email alerts
|

Long period gratings coated with hafnium oxide by plasma-enhanced atomic layer deposition for refractive index measurements

Abstract: Long period gratings (LPGs) are coated with hafnium oxide using plasma-enhanced atomic layer deposition (PEALD) to increase the sensitivity of these devices to the refractive index of the surrounding medium. PEALD allows deposition at low temperatures which reduces thermal degradation of UV-written LPGs. Depositions targeting three different coating thicknesses are investigated: 30 nm, 50 nm and 70 nm. Coating thickness measurements taken by scanning electron microscopy of the optical fibers confirm deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Three samples were measured at the middle position of the precursor inlet and outlet. The measured GPC value appeared to be saturated to ~2.4 Å/cy at a ~0.5 s TDMAHf dose under an O 2 plasma dose time of 60 s. The GPC value in this study was similar to or slightly greater than those reported by other groups [ 11 , 25 , 31 , 32 ]. The refractive index was well saturated to ~1.9 at the same TDMAHf dose time of 2 s, which is similar to the values obtained in well-densified HfO 2 thin films [ 25 , 31 ].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Three samples were measured at the middle position of the precursor inlet and outlet. The measured GPC value appeared to be saturated to ~2.4 Å/cy at a ~0.5 s TDMAHf dose under an O 2 plasma dose time of 60 s. The GPC value in this study was similar to or slightly greater than those reported by other groups [ 11 , 25 , 31 , 32 ]. The refractive index was well saturated to ~1.9 at the same TDMAHf dose time of 2 s, which is similar to the values obtained in well-densified HfO 2 thin films [ 25 , 31 ].…”
Section: Resultssupporting
confidence: 84%
“…The measured GPC value appeared to be saturated to ~2.4 Å/cy at a ~0.5 s TDMAHf dose under an O 2 plasma dose time of 60 s. The GPC value in this study was similar to or slightly greater than those reported by other groups [ 11 , 25 , 31 , 32 ]. The refractive index was well saturated to ~1.9 at the same TDMAHf dose time of 2 s, which is similar to the values obtained in well-densified HfO 2 thin films [ 25 , 31 ]. We also varied the dose time of O 2 plasma with that of TDMAHf maintained at 2 s. While the n values were almost constant regardless of the plasma time, GPC tended to gradually increase from 1.9 Å/cy to 2.4 Å/cy with an increase in the O 2 plasma time.…”
Section: Resultssupporting
confidence: 84%
“…For example, the maximum RI sensitivity of ∼2,500 nm/RIU was achieved at the transition point for a 204-nm-thick-polystyrene(PS)-film-coated LPFG [349]. Melo et al investigated a two-step MT in a hafniumoxide(HfO 2 )-coated LPFG and an RI sensitivity of over 4,000 nm/RIU was achieved [350].…”
Section: Wavelength (Nm)mentioning
confidence: 99%
“…The difference between the maximum and minimum sensitivities within this range is only 2.5%, indicating that the z-shaped fiber interferometer possesses a good fabrication tolerance to the inaccuracy of the bent angles. Finally, it is worth mentioning that in addition to the two bends in the studied z-shaped fiber interferometer, the interferometric concept can be extended by designing different so-called first splitting and second combining schemes, such as utilizing LPFG, TFBG, micro-taper, and so on, which are capable of converting core and cladding mode to each other [12,13,23]. We will apply these structures and compare their RI sensing performance in our future work.…”
Section: Resultsmentioning
confidence: 99%
“…The implementation of optical fiber sensors is usually based on two mechanisms, which are the evanescent field coupling (EFC) [10] and mode interference (MI) [11], respectively. In recent years, numerous EFC-based fiber configurations were proposed, for example by utilizing the long period fiber grating (LPFG) [12], the tilted fiber Bragg grating (TFBG) [13] and the surface plasmon resonance (SPR) [14]. LPFG and TFBG operate in the evanescent field of cladding mode, which exists closing to the fiber surface and easily spreads into the surrounding target solution, thus suffer from a large insertion loss [15].…”
Section: Introductionmentioning
confidence: 99%